Therapeutic opportunities for targeting cold pain pathways - Yin, Kathleen; Zimmermann, Katharina; Vetter, Irina; Lewis, Richard J. (Biochemical Pharmacology, 2015)
Cold pain is a frequent symptom in neuropathic pain. Compared to other pain modalities, such as heat pain, the mechanisms behind physiological and pathological cold pain remain elusive. Moreover, it is becoming increasingly evident that cold pain pharmacology differs between various neuropathic pain conditions, making mechanism-directed treatment based on an understanding of the underlying pathophysiological mechanisms imperative to achieving clinical success. Here we review the processes of physiological and abnormal cold sensing, the pharmacology of cold nociception, cold hyperalgesia and cold allodynia, and provide an overview of cold pain syndromes and their current and potential treatments.
EVALuna2:2485